Key approaches of Ukrainian automotive industry development - Robert Bacho; Бачо Роберт; Bacsó Róbert; Poyda-Nosyk Nina; Пойда-Носик Ніна; Pojda-Noszik Nina (ФОП Лібуркіна Л. М., 2023)
Abstract. The automotive industry of Ukraine is a term that covers a wide range of companies and organizations involved in the design, development, manufacture, marketing and sale of cars, commercial vehicles, trucks and buses, trailers, motorcycles, mopeds, special and military vehicles, machinery, spare parts and components for motorcycles and mopeds. The automotive industry was a rapidly evolving field in Ukraine, and there could be further developments if not the war. Since 2014, Russia’s armed aggression against Ukraine has led to a significant decline in the car industry. The situation much worsened in 2022 when unprovoked and unjustified military aggression of Russia against Ukraine started in February.
Keywords: automotive industry; Ukraine; industrial development; key approaches; innovation